Etude de l’effet insecticide des extraits polyphénols et caroténoïdes de Nerium oleander sur Aphis spiraecola - KEDDAR, Nassima; BELAYACHI, Kheira (My University, 2018)
Secondary plant compounds are often considered to be a defense of the producing plant against various organisms such as pathogens and pests. These compounds are very numerous and varied, and some are widely distributed, such as alkaloids, tannins and terpenes. In order to search for alternatives to chemical control methods, the effect of carotenoids and polyphenols extracted from oleander (Nerium oleander) leaves against Aphis spiraecola aphid was evaluated under laboratory conditions. The active principles with cardiotonic activity present in Nerium oleander are oleandrin (or folinerine), nererin and digitoxigenin. This chemical composition makes oleander a poisonous plant involved in serious or even fatal accidents. The results obtained revealed mortality rates of 81.97% against Aphis spiraecola five days after treatment with the polyphenol extract with the 5% dose. For the doses of 20 and 40%, the mortality rate was 100%, and for the carotenoid the death rate was 100% five days after the treatment. The statistical results showed a very significant variation level p = 0.00 report to the witness. The polyphenolic and carotenoid extracts of N. oleander leaves have a strong insecticidal effect against A. spiraecola. Therefore, they can be integrated in the fight against crop pests.
Keywords: Nerium oleander; Aphis spiraecola; polyphenol; carotenoid extract; insecticide; Nerium oleander; Aphis spiraecola; extrait polyphénoliques; caroténoïdesinsecticide